Enhanced photocatalytic degradation of methylene blue by a direct Z-scheme Bi2S3/ZnIn2S4 photocatalyst - Auttaphon Chachvalvutikul (2018)
© 2018 Elsevier Ltd This study successfully synthesized Bi2S3/ZnIn2S4 composites with different weight percentages of Bi2S3 by cyclic microwave irradiation followed by wet impregnation. The photocatalytic activities of the Bi2S3/ZnIn2S4 composites were evaluated by the photodegradation of methylene blue in an aqueous solution. It was found that the 12.5%wt-Bi2S3/ZnIn2S4 photocatalyst exhibited the highest decolorization efficiency (95.4% within 300 min) with good stability against photocorrosion and good recyclability for photocatalytic reaction. Based on the results from UV–vis DRS, PL, photocurrent response measurement, and the active species trapping experiments, the enhanced photocatalytic activity of the Bi2S3/ZnIn2S4 photocatalyst was due to the increased ability to absorb visible light, and the enhanced charge separation and transportation between Bi2S3 and ZnIn2S4 through the Z-scheme mechanism. A direct Z-scheme charge transfer pathway for photocatalytic reaction over the Bi2S3/ZnIn2S4 photocatalyst was also proposed and discussed.